Pediatric Critical Illness Score, Clinical Characteristics and Comprehensive Treatment of Children with Severe Mycoplasma Pneumoniae Pneumonia - Fang, Chengchao; Mao, Yueyan; Jiang, Mingfen; Yin, Wei (Frontiers in Surgery, 2022)
Objective To investigate the clinical characteristics of children with severe Mycoplasma pneumoniae pneumonia (SMPP) and the correlation with pediatric critical illness score (PICS), and to explore the effect of combined treatment with antibiotics and glucocorticoids. Methods The medical records of 120 children with SMPP admitted to our hospital from January 2020 to June 2021 were retrospectively analyzed. Children with a PICS score greater than 80 within 24 h of admission were included in the non-critical group, those with a score of 71–80 were included in the critical group, and those with a score of ≤70 were included in the extremely critical group. The relevant clinical data and examination indicators of the three groups of children were intercepted and compared. Univariate and multifactorial logistic regression analyses were performed to analyze the correlation between clinical characteristics of children with SMPP and PICS. According to the different treatment methods, the children were subdivided into the control group (n = 54) who received antibiotics alone and the comprehensive group (n = 66) who received antibiotics combined with glucocorticoid therapy. The erythrocyte sedimentation rate (ESR), inflammation and immune indexes, symptom relief or disappearance time, hospitalization days, and clinical efficacy were compared between the two groups before and after treatment. Result Within 24 h of admission, among the 120 children with SMPP, 79 had PICS >80, 32 had PICS 71–80, and 9 had PICS ≤70. Before discharge, among the 120 children with SMPP, 99 had PICS >80, 17 had PICS 71–80, and 4 had PICS ≤70. Univariate analysis showed that there were no significant differences in gender ratio, ratio of fever duration >10 days, age and WBC among the three groups (p > 0.05), the differences in the ratio of abnormal ECG, the ratio of ≥2 pathogenic infections, the ratio of ≥2 systemic damages, CRP levels, and D-dimer levels were statistically significant when compared among the three groups (p < 0.05). Multivariate Logistic regression analysis showed that the number of Co-systemic damages and the level of D-dimer were negatively correlated with PICS classification (p < 0.05). After medication, ESR, CRP, IL-6, and CD8+ levels decreased and CD4+ and CD4+/CD8+ levels increased in both the control and comprehensive groups, and all changes were significant in the comprehensive group compared with the control group (p < 0.05). The antipyretic time, cough relief time, disappearance time of lung rales and hospitalization days in the comprehensive group were shorter than those in the control group (p < 0.05). The total effective rate of the comprehensive group (95.45%) was better than that of the control group (83.33%) (p < 0.05). Conclusion PICS can effectively reflect the clinical characteristics of children with SMPP. The comprehensive treatment effect of azithromycin combined with glucocorticoid is significantly better than that of azithromycin alone. It can effectively reduce the level of inflammation in children with SMPP, improve the immune function of children, and accelerate clinical recovery. It has promotion value.